2022
DOI: 10.5588/pha.22.0039
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to TB care during the COVID-19 pandemic

Abstract: BACKGROUND: Knowledge about factors influencing access and adherence to TB care, and on the impact of the COVID-19 pandemic on TB care in resource-restricted settings is scarce. We conducted this study in Atsimo-Andrefana, a rural region in southern Madagascar where TB prevalence, poverty and food insecurity rates are high. We aimed to determine facilitators and barriers to access to and provision of TB care in rural Madagascar during the COVID-19 pandemic.METHODS: We conducted qualitative focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This ndings where the workload of health workers and lack of technical staff can be a signi cant barrier to effective TB investigation and diagnosis as documented in previous study [22]. Health workers may be overburdened with other responsibilities, which can lead to delays in TB diagnosis and treatment [22]. Similar ndings where there is low TB detection in rural PHFs was recorded other countries in Africa such as Ghana and Ethiopia.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This ndings where the workload of health workers and lack of technical staff can be a signi cant barrier to effective TB investigation and diagnosis as documented in previous study [22]. Health workers may be overburdened with other responsibilities, which can lead to delays in TB diagnosis and treatment [22]. Similar ndings where there is low TB detection in rural PHFs was recorded other countries in Africa such as Ghana and Ethiopia.…”
Section: Discussionsupporting
confidence: 75%
“…The health facility factors identi ed included high workload, lack of protective gear, medicine stock outs, equipment breakdown and power shortages, fear of contacting TB by the Health worker, negative attitude of some health workers and low motivation of staff to manage TB cases. This ndings where the workload of health workers and lack of technical staff can be a signi cant barrier to effective TB investigation and diagnosis as documented in previous study [22]. Health workers may be overburdened with other responsibilities, which can lead to delays in TB diagnosis and treatment [22].…”
Section: Discussionmentioning
confidence: 63%
“…20 studies were from North America [ 32 51 ], 17 from Europe and Central Asia [ 52 68 ], 13 from East Asia and the Pacific [ 69 81 ], five from South Asia [ 82 86 ], 11 from Sub-Saharan Africa [ 87 97 ], three from the Middle East and North Africa [ 98 100 ] and two from Latin America and the Caribbean [ 101 , 102 ]. According to the World Development Indicators 2022–2023 of the World Bank [ 103 ], 45 of the included studies were from high-income countries [ 32 69 , 71 74 , 77 , 79 , 81 ], five were from upper-middle-income countries [ 70 , 75 , 78 , 101 , 102 ], 10 were from lower-middle-income countries [ 76 , 82 86 , 88 , 97 , 99 , 100 ] and 10 were from low-income countries [ 87 , 89 96 , 98 ]. Most participants were young and middle-aged adults, and only 10 studies focused on older people [ 33 , 38 , 41 , 45 , 70 , 71 , 74 , 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most participants were young and middle-aged adults, and only 10 studies focused on older people [ 33 , 38 , 41 , 45 , 70 , 71 , 74 , 77 79 ]. Five studies did not report detailed information regarding participants’ age [ 40 , 64 , 96 , 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…These include barriers that aligned with our phone questionnaire data such as transportation challenges, and costs of medications but also described new barriers such as increasing cost of living, fear of COVID-19 infection at health centers, the stigma of respiratory symptoms, and decreased accessibility of healthcare workers. This builds on the findings from prior qualitative studies in Madagascar and Brazil that identified barriers to TB care during the COVID-19 pandemic as stigma, treatment costs such as transportation and medications, food insecurity [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 96%